Penciptaan Outer Batik Dengan Teknik Batik Tulis, Shibori dan Ecoprint - Nabilla Zalfa; Sri Wiratma; Raden Burhan S, N, D (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
The creation of batik outerwear combines three techniques: hand-drawn batik (batik tulis), shibori, and ecoprint, to produce designs that are both functional and aesthetically rich, while promoting local cultural identity. The process follows the Art Creation Methodology, consisting of four stages: exploration, experimentation, realization, and evaluation. In the exploration phase, the techniques used are studied, and how their combination can create unique motifs. This phase also includes an in-depth understanding of the history and philosophy of each technique, ensuring a strong foundation for their application in the design of the outerwear.In the experimentation phase, various patterns, colors, and compositions are tested to determine the best combination of the three techniques. This stage involves creating several design samples to test the harmony between hand-drawn batik, the visually appealing folds of shibori, and the natural impressions left by ecoprint leaves. Then, in the realization stage, the batik outerwear is completed by integrating these elements into a cohesive design. The techniques of batik tulis, shibori, and ecoprint work together to create rich textures and motifs.In the evaluation phase, the aesthetic and functional quality of the final product is assessed. The final result demonstrates that combining these techniques not only creates unique designs but also adds value in terms of beauty and sustainability, while supporting the preservation of local culture through innovation in batik art.